THE ETHICS OF TRANSPARENCY: EVALUATING THE IMPACT OF OPEN GOVERNMENT DATA ON PUBLIC TRUST AND BUREAUCRATIC ACCOUNTABILITY IN EMERGING ECONOMIES - Mulyaningsih Mulyaningsih; Nadiah Ismail; Ahmad Zainal (Scientechno: Journal of Science and Technology, 2026)
Open Government Data (OGD) has gained significant attention as a tool for promoting transparency, enhancing public trust, and improving bureaucratic accountability. However, the impact of OGD on these factors, particularly in emerging economies, remains underexplored. This research investigates the ethical implications and effectiveness of OGD in fostering trust and accountability within the public sector in emerging economies. The primary objective is to evaluate how OGD influences public trust in government and the accountability of bureaucratic systems. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews across five emerging economies. The findings suggest that while OGD can improve public trust and bureaucratic accountability, its effectiveness is highly contingent on the strength of the institutional context. Countries with stronger democratic frameworks and institutional capacity experienced greater improvements in trust and accountability, while weaker institutions limited OGD’s impact. The study concludes that OGD alone does not automatically lead to increased transparency; instead, institutional readiness and capacity play critical roles in determining its success. This research contributes to the literature by offering a nuanced understanding of OGD’s role in enhancing governance in emerging economies, highlighting both its potential and its limitations.